Plasma fibrinogen level is independent risk factor associated with the incidence of pulmonary infection in patients with spinal cord injury: a retrospective cohort study - Jinlong Zhang; Cheng Wang; Chengqi He (BMC Pulmonary Medicine)
Abstract Background Patients with spinal cord injury (SCI) are at higher risk of developing pulmonary infection (PI), and plasma fibrinogen level may be an independent risk factor for PI. However, the relationship between fibrinogen level and PI incidence in the SCI population remains unclear. This study aimed to elucidate the association between plasma fibrinogen level and the occurrence of PI among SCI patients. Methods We conducted a retrospective analysis of 576 SCI patients admitted to the Rehabilitation Medicine Department between January 1, 2017, and December 31, 2021. Following exclusions, 491 patients were included in the final analysis, with 139 PI cases identified. Results Surgery, level of injury and chest comorbidities were covariates in the relationship between fibrinogen level and PI incidence. Other identified potential risk factors for PI included age, D-dimer level, urinary tract infections (UTI), deep vein thrombosis (DVT), anticoagulant therapy, injury mechanism, and the American Spinal Injury Association Impairment Scale (AIS) grades. After adjusting for these factors, we found that for every 1 g/L increase in fibrinogen level, the risk of developing PI increased by 18% (HR = 1.18, P = 0.011), and indicating a positive linear relationship between fibrinogen level and PI incidence. Conclusion Plasma fibrinogen was an independent risk factor for PI in patients with SCI, especially for AIS-B and C grades. Proactive management of fibrinogen level after admission to rehabilitation medicine department could be crucial in reducing the incidence of PI in this vulnerable population. Clinical trial number Not applicable.